Design of steam-assisted temperature vacuum-swing adsorption processes for efficient CO2 capture from ambient air. (March 2021) - Zhu, Xuancan; Ge, Tianshu; Yang, Fan; Wang, Ruzhu
Abstract: Direct air capture (DAC) is an efficient, negative-carbon-emission technology that enables the capture of distributed emissions and removes location restrictions on capture facilities. However, current DAC demonstration plants are still too costly to be commercialized. In this work, a three-step steam-assisted temperature vacuum-swing adsorption (S-TVSA) cycle based on a packed column was designed for use in DAC systems, and the CO2 and H2 O capacities and kinetics of the adsorbents were considered in detail. By operating the steam purge step at reduced pressures, steam at temperatures lower than 100 °C can be supplied by cheap thermal sources. In addition, the adsorption of H2 O during the steam purge step can release heat for CO2 regeneration. Parameter sensitivity analysis reveals the trade-off relationship between the performance and energy consumption of DAC system with the S-TVSA cycle. The optimal case with a variational steam purge step operating at 90 °C and 0.3 bar achieves a CO2 productivity of 4.45 mol kg −1 day −1 and an energy requirement of 0.295 MJ mol −1 . If the heat energy for the purge steam comes from solar energy or low-grade industrial waste heat, which represents 80.6% of the total energy consumption, the DAC system with S-TVSA cycle will be competitive with post-combustion CO2 capture technologies. Note that the productivity can be increased by up to 280% with only 32.8% of the initial energy consumption by using novel adsorbents with higher capacities and kinetics, potentially making S-TVSA cycles highly efficient for DAC systems. Highlights: A three-step steam-assisted temperature vacuum-swing adsorption cycle was proposed for direct air capture of CO2 . Detailed column equations and CO2 /H2 O adsorption capacities and kinetics of adsorbents were considered. Optimized cases achieved a productivity of 4.45 mol kg −1 day −1 and an energy requirement of 0.295 MJ mol −1 . The heat energy for the purge steam can be supplied by solar energy or low-grade industrial waste heat. The productivity remarkably increases by 280% with reduced energy consumption by using novel adsorbents.